2020
DOI: 10.1186/s12916-020-01665-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: a retrospective cohort study with focus on the over-80s and hospital-onset disease

Abstract: Background Data from the UK COVID-19 outbreak are emerging, and there are ongoing concerns about a disproportionate effect on ethnic minorities. There is very limited information on COVID-19 in the over-80s, and the rates of hospital-onset infections are unknown. Methods This was a retrospective cohort study from electronic case records of the first 450 patients admitted to our hospital with PCR-confirmed COVID-19, 77% of the total inpatient caseload to date. Demographic, clinical and biochemical data were ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 13 publications
6
74
2
Order By: Relevance
“…Overall in hospital mortality was 34.6% which re ects the severity of the disease and the older age of our population and is similar to mortality reported in other studies [22][23]. Frail patients were more likely to die than non-frail patients and a dose response relationship was observed between frailty and mortality which persisted after adjustment for age, sex, illness acuity and multimorbidity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall in hospital mortality was 34.6% which re ects the severity of the disease and the older age of our population and is similar to mortality reported in other studies [22][23]. Frail patients were more likely to die than non-frail patients and a dose response relationship was observed between frailty and mortality which persisted after adjustment for age, sex, illness acuity and multimorbidity.…”
Section: Discussionsupporting
confidence: 87%
“…Frail patients were more likely to die than non-frail patients and a dose response relationship was observed between frailty and mortality which persisted after adjustment for age, sex, illness acuity and multimorbidity. This nding has not been consistent across all recent reports, with some supporting our ndings [22,33] and others either equivocal [27] or failing to nd an association [28]. Intuitively, we would expect to nd an association between a clinical syndrome such as frailty, which is de ned by the presence of low physiological reserve and 'vulnerability', and mortality from an acute severe viral illness such as COVID-19.…”
Section: Discussioncontrasting
confidence: 76%
“…A total of 18,728,893 patients from 50 papers were included in the meta-analyses after excluding any missing data within the studies; 14,506,023 (77%) were White; 1,267,802 (7%) were Asian; 527,944 (3%) were Black, 1,578,192 (8%) were Hispanic, 1,113 were Native American, 229,822 (2%) were Mixed, and 617,997(3%) were of Other ethnic group [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , 81] .…”
Section: Resultsmentioning
confidence: 99%
“…These findings add to emerging reports quantifying the relationship between frailty and mortality in COVID-19. In another London hospitalised cohort, crude deaths in COVID-19 were higher in patients who were frailer (median Clinical Frailty Scale score of 5 versus 4, p = 0.01) [ 13 ]. Other UK case series have shown that patients who died without ventilatory support had a median Clinical Frailty Scale score of 7 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%